2015
DOI: 10.1177/0961203315624022
|View full text |Cite
|
Sign up to set email alerts
|

Systemic lupus erythematosus patients with past neuropsychiatric involvement are associated with worse cognitive impairment: a longitudinal study

Abstract: Longitudinal studies on cognitive impairment in patients with past history of neuropsychiatric lupus (NPSLE) are scant. In this study, NPSLE patients and matched disease and healthy controls were examined with a full battery of neuropsychological tests that covered eight cognitive domains at two time-points 12 months apart. Confounders, including depressive and anxiety symptoms, were measured by the Hospital Anxiety and Depression Scale. Eighteen NPSLE, 18 patients with systemic lupus erythematosus (SLE) who h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
1
4

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 36 publications
(62 reference statements)
1
21
1
4
Order By: Relevance
“…[ 22 25 ] Taken together, these studies suggested that CI is a relatively consistent and stable finding in SLE patients. [ 22 25 ] Nonetheless, longer follow-up may better depict the evolvement of this neuropsychiatric manifestation.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…[ 22 25 ] Taken together, these studies suggested that CI is a relatively consistent and stable finding in SLE patients. [ 22 25 ] Nonetheless, longer follow-up may better depict the evolvement of this neuropsychiatric manifestation.…”
Section: Introductionmentioning
confidence: 81%
“…To sum up, in most of the studies a fluctuating or stable trend was identified more frequently than worsening. [ 22 25 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2932 Prospective neuropsychological studies in SLE have either suggested persistent, emergent, and improved cognition at one to five year intervals, but many methodological issues limit the utility of these findings. 33–38 Finally, in a recent study of 18 NP SLE patients matched with 18 SLE patients without NP, 13 subjects from each group were re-evaluated after one year; 39 the non-NP SLE patients showed statistically significant improvement in attention and visuoconstruction whereas the NP SLE group showed no improvement.…”
Section: Introductionmentioning
confidence: 99%
“…These results concur with other studies, for example, SS patients were found to have no significant cognitive decline over the course of 8 years (Martinez et al , ). Moreover, one study observing CI in systemic lupus erythematosus observed fluctuating, improving or stable trends more frequently than worsening CI over time (Gao et al , ). These disparities in findings suggest that the CFQ may not be sensitive to low levels of change in CI severity.…”
Section: Discussionmentioning
confidence: 99%